Selection of sustainable technologies for reducing emission of volatile organic compounds and greenhouse gases. (May 2019) - Shareefdeen, Zarook
Selection of sustainable and environmental friendly technologies is very important in meeting strict environmental regulations on industrial emissions of volatile organic compounds and greenhouse gases. Many of the industrial volatile organic compounds are toxic and carcinogenic, and they are regulated under Clean Air Act for hazardous air pollutants. Similarly, global environmental agreements such as European Union's 2015 Paris Agreement and Kyoto Protocol restrict carbon emission, which is responsible for global warming, sea-level rise, flooding, and ecological imbalance. It is essential that industries choose suitable technologies that reduce not only toxic volatile organic compounds in the air but also greenhouse gas emissions. In this communication, biotechnological methods are discussed and compared with conventional processes, which are used for control of volatile organic compounds. The readers may find this article useful in the selection of an appropriate technology for their application while minimizing the greenhouse gas emissions.